(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
When tuberculosis is accompanied by urological diseases, changes in the patient’s overall condition, as well as in the immune system, are observed. This is mainly characterized by a profound total secondary immunodeficiency of the T-cell system. When tuberculosis and urological diseases coexist, significant acute changes in the B-cell branch of the immune system (humoral immunity) were not observed, indicating that urological diseases do not have a practical negative impact on the B-cell branch of the immune system and that they are not a complicating factor for pulmonary tuberculosis in terms of humoral immunity.